Reliable adherence to a COPD care bundle mitigates system-level failures and reduces COPD readmissions: a system redesign using improvement science. Issue 11 (21st July 2017) - Zafar, Muhammad Ahsan; Panos, Ralph J; Ko, Jonathan; Otten, Lisa C; Gentene, Anthony; Guido, Maria; Clark, Katherine; Lee, Caroline; Robertson, Jamie; Alessandrini, Evaline A
Abstract : Background: Readmissions of chronic obstructive pulmonary disease (COPD) have devastating effects on patient quality-of-life, disease progression and healthcare cost. Effective interventions to reduce COPD readmissions are needed. Objectives: Reduce 30-day all-cause readmissions by (1) creating a COPD care bundle that addresses care delivery failures, (2) using improvement science to achieve 90% bundle adherence. Setting: An 800-bed academic hospital in Ohio, USA. The COPD 30-day all-cause readmission rate was 22.7% from August 2013 to September 2015. Method: We performed a cross-sectional study of COPD 30-day readmissions from October 2014 to March 2015 to identify care delivery failures. We interviewed readmitted patients with COPD to identify their needs after discharge. A multidisciplinary team created a care bundle designed to mitigate system failures. Using a quasi-experimental study and 'Model for Improvement', we redesigned care delivery to improve bundle adherence. We used statistical process control charts to analyse bundle adherence and all-cause 30-day readmissions. Results: Cross-sectional review of the index (first-time) admissions revealed COPD was the most common readmission diagnosis and identified 42 system-level failures. The most prevalent failures were deficient inhaler regimen at discharge, late or non-existent follow-up appointments, and suboptimal discharge instructions. Patient interviews revealed confusing discharge instructions, especially regarding inhaler use. The COPD care-bundle components were: (1) appropriate inhaler regimen, (2) 30-day inhaler supply, (3) inhaler education on the device available postdischarge, (4) follow-up within 15 days (5) standardised patient-centred discharge instructions. The adherence to completing bundle components reached 90% in 5.5 months and was sustained. The COPD 30-day readmission rate decreased from 22.7% to 14.7%. Patients receiving all bundle components had a readmission rate of 10.9%. As a balancing measure for the targeted reduction in readmission rate, we assessed length of stay, which did not change (4.8 days before vs 4.6 days after; p=0.45). Conclusion: System-level failures and unmet patient needs are modifiable risks for readmissions. Development and reliable implementation of a COPD care bundle that mitigates these failures reduced COPD readmissions.